KEHIDUPAN PENCARI BATU DI SUNGAI KAMPAR (Studi Kasus Penambang Pendatang Di Kelurahan Langgini Kecamatan Bangkinang Kota) - Zainal Askar; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
C excavation business basically contributes positively to society with open employment for them so as to increase income to improve the family economy. In Langgini Village, there are 23 stone seekers, the majority of them are from North Sumatra and are ethnic nias. This study aims to find out the activities and social economic conditions of stone seekers. Using a descriptive qualitative approach to subject selection using purposive means. The results of the study that the length of work looking for stones ranged from 5 years to 19 years. The first cause of the migrant tribe from north Sumatra came to look for rocks in the first kampar river because finding work there was very difficult coupled with the natural disaster of the earthquake that occurred in 2004, and the beginning of their work in the village was rice farmers since the earthquake and the cliffs sawa they collapsed all. They are fully engaged on a normal day from 08:00 to 17:00. The collected stones are sold for 40 thousand for a canoe and in a week workers can collect income up to 480 thousand and can be grouped into families with sufficient standard of living.  Keywords: Excavation C, Stone Seeker, Langgini Village